Resource revenue model for a developed country: case of Estonia. Ressursitulu mudel arenenud riigile: Eesti kaasus - Kallemets, Kalev (Estonian Discussions on Economic Policy, 2015)
The main objective of this paper is to find appropriate parameters for a resource revenue fund model in the industrial part of the World, with Estonia as an example. Based on literature review and case studies of resource revenue funds, four parameters are suggested: the period of resource revenue flow, the magnitude of the revenue flow relative to GDP, relative development level of the country and institutional development level. Additionally, four resource revenue fund models are characterized: fiscal, mixed, Permanent Income Fund and Sovereign Development Fund. Analysis shows that for a country where the main natural resource is oil shale (as is the case in Estonia), the most suitable resource revenue fund model would be a blend of fiscal modelling and Sovereign Development Fund.